(untitled) ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2023)
Nonetheless, reading a literary work in an English class requires you to read in a unique way: you must conduct literary analysis. Analyzing something entails disassembling it into smaller components and analyzing each one’s function separately and collectively. Examining every component of a play, poem, short story, or novel—character, setting, tone, and imagery, for example—and considering how the author employs each component to achieve specific effects is known as literary analysis. A literary essay differs from a book review in that it does not inquire about your opinion of the book or whether you would suggest it to another reader. A literary essay differs from the type of book report you may have written in school, where you were required to provide an overview of the plot. "How does this piece of literature actually work?" is the question posed in a literary essay for high school or college. "Why might the author have made the choices he or she did?" and "How does it do what it does?"